DATA BASE COMPILATION OF TRIGLYCERIDE COMPONENTS IN 21 KINDS OF FRUITSÃâÃâ SEED AND NUTS - BILL J.T.( NIM : 20511015) ; Pembimbing I : Dr. Suryo Gandasasmita; Pembimbing II : Pr, MANGINDAAN
Seeds and nuts oils are very interesting to be studied and characterized because some of them are essential for food and medicinal application. In addition, these oils can be used as an alternative fuel, cosmetics, health products, and lubricants. Seeds and nuts are rich in fats/oils. Fats/oils content in seeds and nuts are usually in the form of triglycerides. The aim of this study is to analyze the composition of the triglycerides in fruit seeds and nuts. Triglyceride composition in fruit seeds and nuts may vary. Oils in fruit seeds and nuts were extracted by maceration with n-hexane. The crude extract can be directly analyzed without prior purification. One of the recent methods used to analyze the composition of triglycerides in oils qualitatively is the use of Electrospray Ionization - Ion Trap - Mass Spectrometry (ESI-IT-MS). Triglycerides can not be analyzed directly by ESI-IT-MS because triglycerides are difficult to be ionized. One approach used in this study is the addition of Ag+ cations to form coordination bond with triglycerides. The presence of Ag+ cations in triglycerides can provide a positive net charge in triglycerides so that triglycerides can be detected by the mass detector. Signal in the mass spectrum that correlated with the[triglycerides + Ag]+ species can be fragmented. The fragmentation data are used for analysis of fatty acids sequence in triglycerides. With the hypothesis that the fatty acid that bound to glycerol in second carbon position (R2) relative to glycerol is unchangeable during fragmentation, triglyceride structure could be determined. Fragmentation assumed to occur only towards fatty acids bound to glycerol at the first (R1) and third (R3) carbon positions. Using these assumptions related to fragmentation, the sequence of the fatty acid constituents of a triglyceride could be determined. Twenty seven samples of fruit seeds and nuts were analyzed in this study. Such analysis using this method gave satisfied result. However, among the 27 oils, not all components of triglycerides in the oil can be detected using the addition of Ag+ cations as an ionization mediator. In general, a chemical species could be detected when it forms coordination bonding with Ag+ cations. Triglyceride components in some fruit seeds and nuts have been successfully analyzed. In this study, a certain tendency was observed in the pattern of the position of oleic acid in a triglyceride relative to glycerol. Oleic acid tends to occupy the position of second carbon position of glycerol (R2) in triglycerides. However, the position of oleic acid was also found in the first (R1) or the third (R3) carbon position of glycerol in a triglyceride. Mostly, fruit seeds and nuts have a similar composition of triglyceride components. There are also unusual (“exotic”) several types of fatty acid constituent of triglycerides that in some fruit seeds and nuts. “Exotic” fatty acids found in this study is a fatty acid having an odd number of carbon atoms (C13 and C19), or fatty acid that have carbon atom number greater than 18 (icosanoic acid (C20), docosanoic acid (C22), and tetracosanoic acid (C24)), or fatty acids with unusual double bonds of fatty acids such as C12:1, C13:1 and C13:2. The samples found to have “exotic” fatty acids are tamarind, starfruit, melon, brown, tomato seeds, soybeans, cashews nuts, and peanuts. In this study, there are also some samples of fruit seeds in which triglyceride components that have not been successfully detected. Such seeds are nutmeg, avocado, pomegranate, durian, papaya, and soursop seeds. In summary, this research contributes on the effort for data base compilation of triglyceride composition in fruit seeds and nuts.